Impact of Tourism on Saudi Arabian Society - Waleed Mohammed A. Alabdulrazaq (International Journal of Asia Pacific Studies, 2026)
The tourism sector in Saudi Arabia has experienced major changes in line with Vision 2030, which aims to expand the industry from religious travel to a larger market for leisure and heritage activities. One of the major factors affecting policy implementation is the lack of qualitative information on tourism’s effects on Saudi tradition. This study explores the social and cultural impact of tourism on Saudi society within the framework of the Vision 2030. This study adopted a qualitative research design and used semi-structured interviews with residents of Saudi Arabia, tourists from different countries in Saudi Arabia, stakeholders from the tourism sector in Saudi Arabia, and two experts from the university. Fifteen interviews were conducted in total, which provides extensive knowledge about the nature of tourism in Saudi Arabia and its impact on society. The findings demonstrate that Saudi Arabia’s tourism industry supports economic development, improves international connections, and promotes modernisation. However, issues surrounding the loss of traditional authenticity, the preservation of social norms, and religious tolerance remain at the forefront of the industry’s expansion. This study demonstrates the need for Saudi Arabia to adopt a balanced approach that supports sustainable tourism while preserving its traditional heritage.